Sistem dan fungsi Muscular - Yonny Herdyanto, (Kepelatihan Olahraga, 2010)
Based on morphological shape, and location of work systems in the body, muscles are divided into three, namely striated muscle, smooth muscle, and heart muscle. Also called striated muscle or muscle skeletal muscle fiber cross. These muscles work under consciousness. In striated muscle, fibrils-fibrilnya have transverse lines dark (anisotrop) and light (isotrop) arranged criss-hose. Layer of fibrous connective tissue covering every muscle and into the inside to coat the fasikel. This network channeling of nerve impulses and blood vessels into the muscle and mechanically transmit power from one end of the contraction of muscle to the other end. Smooth muscle is also called involuntary muscle or muscle tool in (visceral muscle). Composed of smooth muscle cells - spindle-shaped cells smooth. Each - each cell has one core that is located in the middle. Smooth muscle contraction is not according to the will, but are supplied by autonomic nerves. Factors that affect visceral smooth muscle contraction is certain hormones, local metabolic intermediate produced in the surrounding muscle, mechanical stretch, and some types of drugs. Cardiac muscle is a combination of skeletal muscle and smooth muscle, arranged in a pattern miofilamen regular pemitaan that berlurik heart muscle. Unlike skeletal muscle, some calcium ions are released and used to trigger a contraction derived from the extracellular fluid, as a result of the heart muscle becomes very sensitive to the imbalance of calcium in body fluids. Skeletal muscles always work in groups and not alone. Some muscles contract in a group while the other group relaxes. The nature of work divided into antagonistic muscle and synergistic. From the results of research and observations with the electron microscope and X-ray diffraction, Hansen and Huxly (l955) put forward the theory of muscle contraction called a model of sliding filaments. This model states that contraction based on the existence of two sets of filaments in the contractile muscle cells that form the actin filament and myosin filament .. Stimulation received by acetylcholine causes shrinking aktomiosin (contraction).